The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jon.12810
|View full text |Cite
|
Sign up to set email alerts
|

Improved Reliability of Automated ASPECTS Evaluation Using Iterative Model Reconstruction from Head CT Scans

Abstract: Iterative model reconstruction (IMR) has shown to improve computed tomography (CT) image quality compared to hybrid iterative reconstruction (HIR). Alberta Stroke Program Early CT Score (ASPECTS) assessment in early stroke is particularly dependent on high-image quality. Purpose of this study was to investigate the reliability of ASPECTS assessed by humans and software based on HIR and IMR, respectively. METHODS: Forty-seven consecutive patients with acute anterior circulation large vessel occlusions (LVOs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…Even though the differences regarding imaging quality and conspicuity of ischemic areas are minor, the inter-reader agreement in the blinded rating of both raters was substantial to almost perfect for most evaluated items and scans, except for evaluations of GM/WM differentiation using SD imaging data with model-based iterative reconstruction. In this regard, previous research has already suggested that the performance of human readers for assessing ischemic demarcation can depend on the algorithm used for MDCT image reconstruction, with a trend towards better agreement for more established reconstruction algorithms (i.e., hybrid algorithms) with the experience of the reader 41 . Thus, a comparable result may be present for ratings of GM/WM differentiation in SD imaging data with model-based iterative reconstruction, which might be interpreted as an analogous trend to higher variation between readers for the more recently introduced model-based iterative image reconstruction algorithm over the more established hybrid algorithm.…”
Section: Discussionmentioning
confidence: 96%
“…Even though the differences regarding imaging quality and conspicuity of ischemic areas are minor, the inter-reader agreement in the blinded rating of both raters was substantial to almost perfect for most evaluated items and scans, except for evaluations of GM/WM differentiation using SD imaging data with model-based iterative reconstruction. In this regard, previous research has already suggested that the performance of human readers for assessing ischemic demarcation can depend on the algorithm used for MDCT image reconstruction, with a trend towards better agreement for more established reconstruction algorithms (i.e., hybrid algorithms) with the experience of the reader 41 . Thus, a comparable result may be present for ratings of GM/WM differentiation in SD imaging data with model-based iterative reconstruction, which might be interpreted as an analogous trend to higher variation between readers for the more recently introduced model-based iterative image reconstruction algorithm over the more established hybrid algorithm.…”
Section: Discussionmentioning
confidence: 96%
“…NBC software is now available at our hospital for automatic calculation of ASPECTS. In addition, there are available options for various parameters of NCCT images (e.g., slice thickness and reconstruction algorithms) (7,8). Thinner slices and iterative reconstruction have been shown to improve the reliability and performance of automated ASPECTS (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are available options for various parameters of NCCT images (e.g., slice thickness and reconstruction algorithms) (7,8). Thinner slices and iterative reconstruction have been shown to improve the reliability and performance of automated ASPECTS (7)(8)(9). However, some studies have found no significant difference in ASPECTS automatically derived from images with different slice thicknesses (1 mm vs. 2.5 mm, ≤3 mm vs. 3-6 mm) (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations